The Effect Of Motivation on Employee Satisfaction at Cv Indorent Utama - Tri Prabowo (International Journal of Education, Information Technology, and Others, 2022)
The purpose of this study was to determine the effect of motivation on employee job satisfaction at CV. Main Indorent. The sample in this study were employees of CV. Indorent Utama a total of 20 people using interviews, observation, and questionnaires. The results showed that the influence of external motivation on job satisfaction was very high compared to internal motivation. The relationship of external motivation to job satisfaction greatly affects the increase in employee performance as much as 54.3%. In this study, the external motivation that most influences the improvement of employee performance is good communication between employees and superiors, a good work environment, and superiors always give praise. The three main factors that can improve employee performance in completing tasks. Meanwhile, from the respondents' responses, the relationship between internal motivation and employee performance was an average of 58%. In this study, the three main factors of internal motivation that influence job satisfaction are job performance, satisfaction in completing tasks, and interesting work